Returning to Wild? Four Lions’ Journey from Circus to “Sanctuary” - Vander Meer, Elizabeth (Humanimalia, 2019)
Four lions, Skinny, Little, Sid and Sammy, have been subjected to dramatic changes as a result of a shifting political landscape. Each experienced a life of performance in a travelling French circus until authorities seized them in Belgium after the country enacted a ban on use of wild animals in circuses in 2014. The lions then spent almost two years in temporary rescue in Belgium awaiting transport to a permanent home at a UK zoo. These lions as individuals and their movement from circus to “sanctuary” with a conception that they are being returned to a more “wild life” are the subject of this multi-species, multi-sited ethnography. The temporary rescue context is considered in terms of animal viewing, lion-human interactions and particular physical spaces of captivity, while findings in circus and zoo sites serve as comparison and contrast.